Non-lethal imaging and modeling approaches for estimating dry mass in aquatic larvae - Daniela Granados Frias; Najva Akbari; Lauren A. O’Connell; Bryan H. Juarez (PLoS ONE, 2026)
Body mass is crucial for scaling and comparing physiological rates. Specifically, dry body mass is important in determining an organism’s metabolic rate since it excludes metabolically inactive water weight. While obtaining repeated measurements of body mass throughout an individual’s lifetime is trivial, we can obtain only a single estimate of dry body mass since classical methods require end-point euthanasia. Here, we present imaging and modeling techniques for estimating individual dry body mass in African clawed frog ( Xenopus laevis ) tadpoles, which allow repeated sampling of the same individuals. We applied allometric principles and tested whether external anatomy would yield reliable estimates of dry body mass. Specifically, we describe a procedure to embed tadpoles in agarose media for obtaining morphological data in 3-D and then we evaluate dry mass predictions among nine cross-validated maximum likelihood and machine learning models. The best performing and most flexible model was an allometric model that used estimates of body volume to predict dry body mass. However, other models based on wet body mass or fewer input variables may also be logistically tractable. This research develops a foundation for continued research on the biological importance of dry body mass, particularly in the context of development and physiological ecology.